2022
DOI: 10.3389/fnmol.2022.1009976
|View full text |Cite
|
Sign up to set email alerts
|

Human stefin B: from its structure, folding, and aggregation to its function in health and disease

Abstract: Mutations in the gene for human stefin B (cystatin B) cause progressive myoclonic epilepsy type 1 (EPM1), a neurodegenerative disorder. The most common change is dodecamer repeats in the promoter region of the gene, though missense and frameshift mutations also appear. Human stefin B primarily acts as a cysteine cathepsin inhibitor, and it also exhibits alternative functions. It plays a protective role against oxidative stress, likely via reducing mitochondrial damage and thus generating fewer mitochondrial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 107 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…21 Other functions include regulation of microglial activation and (neuro) in ammation, organizing synaptic transmission, interneuron migration, and chromatin structure during neural stem cell renewal and differentiation, prevention of oxidative stress induced cell death, and alteration of malignant characteristics of cancers. 14,[22][23][24][25][26][27] Consistent with its functional plurality, the CSTB protein has been documented in multiple subcellular locations, including at the lysosomal surface, in the lysosome, nucleus, and cytosol, and most recently, secreted extracellularly. 6,22,25,28 The speci c function of CSTB that contributes most prominently to ULD is unknown, which has been an impediment to developing disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Other functions include regulation of microglial activation and (neuro) in ammation, organizing synaptic transmission, interneuron migration, and chromatin structure during neural stem cell renewal and differentiation, prevention of oxidative stress induced cell death, and alteration of malignant characteristics of cancers. 14,[22][23][24][25][26][27] Consistent with its functional plurality, the CSTB protein has been documented in multiple subcellular locations, including at the lysosomal surface, in the lysosome, nucleus, and cytosol, and most recently, secreted extracellularly. 6,22,25,28 The speci c function of CSTB that contributes most prominently to ULD is unknown, which has been an impediment to developing disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 99%
“…14,[22][23][24][25][26][27] Consistent with its functional plurality, the CSTB protein has been documented in multiple subcellular locations, including at the lysosomal surface, in the lysosome, nucleus, and cytosol, and most recently, secreted extracellularly. 6,22,25,28 The speci c function of CSTB that contributes most prominently to ULD is unknown, which has been an impediment to developing disease-modifying therapies. A gene-based approach is therefore favored.…”
Section: Discussionmentioning
confidence: 99%
“…The protein inhibits cathepsins L, H and B as well as papain. It is considered a key player in the regulation of cellular proteostasis, protecting against proteases leaking from lysosomes [19], and it is suggested that it also possesses a chaperone-like function [42].…”
Section: The Cstb Proteinmentioning
confidence: 99%